"I only knew how to search Google": students' reflections on a four-year information literacy curriculum. - Sanger, Stephanie; Smith, Denise A. (Journal of the Canadian Health Libraries Association (JCHLA), 2025)
Introduction: For undergraduate general health sciences education, there is insufficient high-quality evidence that speaks to the benefits and challenges of an integrated and scaffolded information literacy (IL) curriculum when compared to more traditional modes of delivery. Calls for scaffolded and curriculum-integrated programs are on the rise. Objectives: This study aims to understand students' perceived confidence and skill levels when engaging with or searching for health information, after four years of IL training. Methods: A mixed-methods survey was used to learn whether or how students' confidence in their IL skills was impacted by an IL curriculum integrated into the Bachelor of Health Sciences (BHSc) program at McMaster University. Quantitative survey questions were analysed with descriptive statistics. Qualitative survey questions underwent three cycles of coding to identify themes in participant responses to open-ended questions. Results: Of 194 fourth-year students, 49 participated in the survey, a response rate of 25%. 79% of participants recalled feeling "unconfident" or "not so confident" in finding information in their first year of study. By their fourth year, all participants indicated they felt "somewhat confident" (53%) or "very confident" (47%). 93% of participants indicated their confidence in searching for information was positively impacted by the mandatory IL curriculum. 90% of participants believed they would use these IL skills after graduation. Conclusion: A mandatory curriculum-integrated IL program in undergraduate health sciences positively impacted students' confidence in searching for and finding information. This study indicates the potential benefits of integrating IL instruction into program-wide curricula for undergraduate students.